Alport syndrome: significance of gingival biopsy in the initial diagnosis and periodontal evaluation after renal transplantation - Hilal Uslu Toygar; Okan Toygar; Esra Guzeldemir; Ulkem Cilasun; Ahmet Nacar; Nebil Bal (University of São Paulo, 2009)
Alport Syndrome (AS) is an important hereditary disorder affecting the glomerular basement membrane. Diagnosis of AS is based on the presence of hematuric nephropathy, renal failure, hearing loss, ocular abnormalities and changes in the glomerular basement membrane of the lamina densa. The aims of this case report were to show the changes in the gingival tissues in a patient with AS under therapy with cyclosporin-A after renal transplantation and to discuss the possible role of type IV collagen in gingival basal lamina as an alternative approach for the diagnosis of AS. A 20-year-old male patient with AS underwent periodontal therapy including a series of gingivectomy surgeries. Gingival samples obtained during the second surgery were examined histopathologically and by transmission electron microscopy for further pathological examination. Gingivectomy procedures have been performed every 6 months over the last 4 years. The excessive and fibrous gingival enlargements resulted in migration of the anterior teeth, but no alveolar bone loss occurred. This is the first report to demonstrate the possible changes in the gingival tissues caused by AS. It is suggested that gingival biopsy can be an initial diagnostic tool instead of renal or skin biopsies. Proper dental and periodontal care and regular visits to the dentist could provide limited gingival hyperplasia to patients with AS.